2021
DOI: 10.35418/2526-4117/v3n1a5
|View full text |Cite
|
Sign up to set email alerts
|

MOLECULAR CHARACTERIZATION OF ELITE LINES OF PAPAYA (Carica papaya L.) VIA SSR MARKERS

Abstract: This study aimed to analyze the genetic variability and to estimate diversity parameters of 23 elite papaya lines based on microsatellite molecular markers. The plant material was composed of elite lines, 18 from the 'Formosa' and five from the 'Solo' group. The expected heterozygosity (HE), observed heterozygosity (HO), and the coefficient of inbreeding (ƒ) for each genotype were estimated. The weighted index obtained the dissimilarity matrix, and the estimated genetic distance was presented graphically throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…Regarding population clusters, it was observed that the groups were formed based on heterotic groups. Such organization enables systematic exploitation of the lines, making them promising in crop breeding programs, thereby corroborating with results demonstrated elsewhere (Pirovani et al 2021, Vivas et al 2018.…”
Section: Molecular Analysis For the Populationsupporting
confidence: 78%
See 1 more Smart Citation
“…Regarding population clusters, it was observed that the groups were formed based on heterotic groups. Such organization enables systematic exploitation of the lines, making them promising in crop breeding programs, thereby corroborating with results demonstrated elsewhere (Pirovani et al 2021, Vivas et al 2018.…”
Section: Molecular Analysis For the Populationsupporting
confidence: 78%
“…An Acad Bras Cienc (2023) 95(1) e20220468 2 | 11 descriptors (Pinto et al 2013, Vivas et al 2018, Pirovani et al 2021. The use of these lines in crossbreeding programs developed 21 hybrid papaya cultivars (Pereira et al 2019a).…”
Section: And Molecularmentioning
confidence: 99%